8.1. FUNCOID INDUCED BY A RELOID

147

Proof.

X ×

RLD

Y 6

f

F

GR

f, P

∈ X ×

RLD

Y

:

P

6

F

F

GR

f, X

∈ X

, Y

∈ Y

:

X

×

Y

6

F

F

GR

f, X

∈ X

, Y

∈ Y

:

Src

f

X

h

FCD

(Src

f

;Dst

f

)

i

Dst

f

Y

F

GR

f

:

X

h

FCD

(Src

f

;Dst

f

)

F

i

Y ⇔

X

[(

FCD

)

f

]

Y

.

Theorem

801

.

(

FCD

)

f

=

d

FCD

xyGR

f

for every reloid

f

.

Proof.

Let

a

be an ultrafilter on Src

f

.

h

(

FCD

)

f

i

a

=

d

h

FCD

F

i

a

F

xyGR

f

by the definition of (

FCD

).

D

d

FCD

xyGR

f

E

a

=

d

h

FCD

F

i

a

F

xyGR

f

by theorem

635

.

So

h

(

FCD

)

f

i

a

=

D

d

FCD

xyGR

f

E

a

for every ultrafilter

a

.

Lemma

802

.

For every two filter bases

S

and

T

of morphisms

Rel

(

U

;

V

) and

every set

A

U

l

RLD

S

=

l

RLD

T

l

V

h

F

i

A

F

S

=

l

V

h

G

i

A

G

T

.

Proof.

Let

d

RLD

S

=

d

RLD

T

.

First let prove that

n

h

F

i

A

F

S

o

is a filter base. Let

X, Y

n

h

F

i

A

F

S

o

. Then

X

=

h

F

X

i

A

and

Y

=

h

F

Y

i

A

for some

F

X

, F

Y

S

. Because

S

is a filter base,

we have

S

3

F

Z

v

F

X

u

F

Y

. So

h

F

Z

i

A

v

X

u

Y

and

h

F

Z

i

A

n

h

F

i

A

F

S

o

. So

n

h

F

i

A

F

S

o

is a filter base.

Suppose

X

d

n

V

h

F

i

A

F

S

o

. Then there exists

X

0

n

h

F

i

A

F

S

o

where

X

w

X

0

because

n

h

F

i

A

F

S

o

is a filter base. That is

X

0

=

h

F

i

A

for some

F

S

. There exists

G

T

such that

G

v

F

because

T

is a filter base. Let

Y

0

=

h

G

i

A

. We have

Y

0

v

X

0

v

X

;

Y

0

n

h

G

i

A

G

T

o

;

Y

0

d

n

V

h

G

i

A

G

T

o

;

X

d

n

V

h

G

i

A

G

T

o

.

The reverse

is symmetric.

Lemma

803

.

n

G

F

F

GR

f,G

GR

g

o

is a filter base for every reloids

f

and

g

.

Proof.

Let denote

D

=

n

G

F

F

GR

f,G

GR

g

o

. Let

A

D

B

D

. Then

A

=

G

A

F

A

B

=

G

B

F

B

for some

F

A

, F

B

GR

f

,

G

A

, G

B

GR

g

. So

A

B

(

G

A

G

B

)

(

F

A

F

B

)

D

because

F

A

F

B

GR

f

and

G

A

G

B

GR

g

.

Theorem

804

.

(

FCD

)(

g

f

) = ((

FCD

)

g

)

((

FCD

)

f

) for every composable

reloids

f

and

g

.